2015
DOI: 10.1142/s1363919615500401
|View full text |Cite
|
Sign up to set email alerts
|

New Product Development Success Factors in Prospector Organisations; Mixed Method Approach

Abstract: New product development (NPD) is a path not a destination; a path that organisations, more than ever, should follow to survive in the present unpredictable and dynamic market. Prospector organisations, especially those whom are leaders in their own industrial sector, implement some factors to improve new product success rate. In this regard, by applying a sequential mixed method approach, 13 key factors are identified and categorised into managerial, structural and organisational, process and environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…In this regard, a firm may seek to influence the behavior of the market by developing products with a high degree of novelty or products that activate the latent needs and desires of customers. By regularly developing new products, a firm attempts to not only survive in a changing environment (Kachouie and Sedighadeli, 2015) but also stimulate customers to reconsider their preferences/aversions or encourage customers to reconsider the meaning of certain product attributes. The firm can adopt ideas from other sectors to surprise competitors or may establish new product/technology standards within its own industry sector.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this regard, a firm may seek to influence the behavior of the market by developing products with a high degree of novelty or products that activate the latent needs and desires of customers. By regularly developing new products, a firm attempts to not only survive in a changing environment (Kachouie and Sedighadeli, 2015) but also stimulate customers to reconsider their preferences/aversions or encourage customers to reconsider the meaning of certain product attributes. The firm can adopt ideas from other sectors to surprise competitors or may establish new product/technology standards within its own industry sector.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There are various approaches to NPD best practices; along this vein, Barczak et al (2009), Kahn et al (2012), Markham and Lee (2013) and Holahan et al (2014) aimed to identify these best practices with the support of the knowledge of companies associated with the Product Development and Management Association. Studies such as Chen et al (2007) and Kachouie and Sedighadeli (2015) have used mathematical modeling to identify best practices and assist the decision-making of managers involved with NPD. Some theoretical reviews (Bhuiyan, 2011; Ernst, 2002; Lester, 1998; Majava et al , 2013) have also aimed to present and systematize the successful practices present in the NPD literature.…”
Section: Best Practices In New Product Developmentmentioning
confidence: 99%
“…Moreover, additional practices can also be stimulated by top management to encourage innovation in the NPD such as: recognition and rewarding of employee creativity, the adoption of open innovation practices and collaboration with external partners (other companies, universities, research institutes, consultants and even competitors), intra-entrepreneurship, willingness to take risks and orientation to internationalization (Lester, 1998; Kachouie and Sedighadeli, 2015; Cooper, 2019).…”
Section: Best Practices In New Product Developmentmentioning
confidence: 99%
“…O' Regan and Ghobadian (2005) showed that prospectors tend to intensify their product development in competitive markets. Kachouie and Sedighadeli (2015) show that a prospector with an entrepreneurial structure will be more effective than one without it, because the increase in innovative activities such as investing in research and development increases knowledge sharing, which reduces costs and speeds up the introduction of new products. Similarly, Parnell and Wright (1993) show that prospectors with an entrepreneurial structure will perform better than analysers and defenders in a competitive market because their strategy and structure match significantly better with a competitive market.…”
Section: Prospectormentioning
confidence: 99%